Nonstomatal Inhibition of Photosynthesis in Sunflower at Low Leaf Water Potentials and High Light Intensities - Boyer, J. S. (1971)
The inhibition of photosynthesis at low leaf water potentials was studied in soil-grown sunflower to determine the degree to which photosynthesis under high light was affected by stomatal and nonstomatal factors. Below leaf water potentials of −11 to −12 bars, rates of photosynthesis at high light intensities were insensitive to external concentrations of CO(2) between 200 and 400 microliters per liter. Photosynthesis also was largely insensitive to leaf temperature between 10 and 30 C. Changes in CO(2) concentration and temperature had negligible effect on leaf diffusive resistance. The lack of CO(2) and temperature response for both photosynthesis and leaf diffuse resistance indicates that rates of photosynthesis were not limited by either CO(2) diffusion or a photosynthetic enzyme. It was concluded that photosynthesis under high light was probably limited by reduced photochemical activity of the leaves at water potentials below −11 to −12 bars.